En medeltida massgrav från Sigtuna, Sverige: Tolkning och diskussion kring ett flertal skelett med spår efter trauma - Kjellström, Anna (Hikuin, 2000)
A medieval mass grave from Sigtuna, Sweden. An interpretation and discussion about several individuals with signs of skeletal trauma By Anna Kjellström During the winter and spring of 1998 an archaeological excavation of a medieval churchyard was carried out close to the ruins of the St Lars church in the centre of Sigtuna, Sweden. Remains of several skeletons were found in what seemed to be a large pit. The pit was 4 by 2.5 metres with a depth of 0.3 metres, but the grave had been disturbed by later interference and was probably larger and deeper in its original state. The bodies seemed to have been thrown on top of each other and no direct efforts to arrange the individual body positions could be observed. During the anthropological analysis at least seventeen individuals were identified, men (10 or 11), women (5), and children (1). The individuals were aged from 8-9 to 60 years. The analysis shows that a majority (9) of the skeletons have cut lesions. The answer to the questions about who these people were, what caused their death and why they had to share the same grave are difficult to establish but some clues do exist. Considering that both sexes in a variety of ages are identified without any signs of healed slice wounds, the interpretation of these individuals as representatives of ordinary citizens who lacked earlier experience in combat is possible. The fact that they were buried in a churchyard close to the walls of the southeast corner implies that time was taken to arrange a grave in holy ground, i.e. they were probably not criminals. Probably they all died at the same occasion, possibly during an attack against the town or its surroundings. The frequency of violence lesions makes the hypothesis of an epidemic or a major accident causing the death of the individuals less likely. The remains of these individuals, probably members of the same community, are suited for a variety of different analyses. For instance, DNA-tests on the skeletons may provide information about family relationships. Analyses of stable isotopes and trace elements are planned to be conducted in the future so that standard values and variations within an absolutely contemporary group can be registered. Hopefully the forensic investigation may yield more information about which weapons were used and whether there is a detectable pattern in the way the wounds are located.